Exploring EFL Secondary Islamic Boarding School Students’ Practices and Challenges in Using English as a Classroom Language - Novianti, Vivit Anggun; Pahlevi, Muhammad Reza; Abas, Totoh Tauhidin (Peneliti.net, 2024)
This study focused on investigating the practice of English in EFL classroom and the challenges encountered by EFL students at Islamic Boarding School. Therefore, this study aimed to reveal to what extent students practice English in EFL classroom and the obstacles they encountered. Participants of this study consist of six students from eighth grade. They were recruited voluntarily and based on suggestions from the teacher. This study used a qualitative approach with descriptive case study as the research design. The author used observation, interviews, and documentation to obtain the data. In analyzing the data, the author applied a method by Miles and Huberman (1994) which consist of data reduction, data display, conclusions drawing and verification. For the result, the author found that during the learning process, students practiced English actively during the questioning and answering session, and during the presentation session. Both sessions encouraged students to practice English confidently and fluently. However, some challenges encountered by students in practicing English, such as inhibition consist of being shy to speak English, being afraid to make mistakes, being scared of critique, and being confused about what to say. Moreover, restricted learning time and students’ mother tongue were considered as students’ challenges in practicing English as well.